2012
DOI: 10.1007/s00449-011-0670-4
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid-mediated aldolase immobilisation for enhanced catalysis and thermostability

Abstract: To improve the properties of the immobilised 2-deoxy-D-ribose-5-phosphate aldolase (DERA), unreacted functional groups on support surface were blocked with amino acids. The relative activities of the immobilised enzyme were 144.7 and 141.9% when the post-immobilisation modification was done with Arg and Phe, respectively. The residual activity of immobilised DERA after heating at 60 °C for 120 min was 65.1% when Phe and Val were used as the blocking amino acids, a 2.0- and 2.87-fold increase over that of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Three examples were described with different carriers but always utilizing the amino group of the surface lysines (Wang et al 2012; Fei et al 2014; Reinicke et al 2017). In all cases, the active immobilized DERA displayed improved, but not excellent activity or stability.…”
Section: Acetaldehyde Resistance Of Deramentioning
confidence: 99%
See 1 more Smart Citation
“…Three examples were described with different carriers but always utilizing the amino group of the surface lysines (Wang et al 2012; Fei et al 2014; Reinicke et al 2017). In all cases, the active immobilized DERA displayed improved, but not excellent activity or stability.…”
Section: Acetaldehyde Resistance Of Deramentioning
confidence: 99%
“…This type of protective covalent linking of the enzyme via a tether to the carrier material was also applied to stabilize DERA against high acetaldehyde concentrations. Three examples were described with different carriers but always utilizing the amino group of the surface lysines (Wang et al 2012 ; Fei et al 2014 ; Reinicke et al 2017 ). In all cases, the active immobilized DERA displayed improved, but not excellent activity or stability.…”
Section: Acetaldehyde Resistance Of Deramentioning
confidence: 99%
“…Thus, large quantities of the enzyme are necessary to obtain industrially useful product yields . This issue can be circumvented by improving its resistance and catalytic activity using a molecular evolution approach, or by applying a cell‐free lysate or a whole‐cell biocatalyst instead of an isolated enzyme or by immobilization on appropriate supports …”
Section: Introductionmentioning
confidence: 99%
“…3,6,14,17,20,21,23 This issue can be circumvented by improving its resistance and catalytic activity using a molecular evolution approach, 3,23,26 or by applying a cell-free lysate or a whole-cell biocatalyst instead of an isolated enzyme 4,20 or by immobilization on appropriate supports. [27][28][29][30] In pursuit of finding the most cost-effective configuration for the lactol synthesis, especially for industrial use, it is of great importance for understanding the mechanisms and kinetics of enzyme systems in detail, which can be achieved by applying mathematical modeling techniques. [31][32][33] Although the lack of reports on kinetic data obtained from kinetic models of DERA-catalyzed reactions is evident, 3 some kinetic studies of related aldolase-based syntheses can be found.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been often found after immobilization of enzymes. [29][30][31][32][33] This result might be due to multi-point ionic interaction between the enzyme and the Sepharose matrix containing cationic Ni 2+ ions. In general, the activity of the immobilized enzyme is more resistant than that of the soluble form against heat and denaturing agents.…”
Section: )mentioning
confidence: 99%